PENGARUH KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA PEGAWAI DI LINGKUNGAN KECAMATAN BANTARGEBANG KOTA BEKASI - Heru Dian Setiawan (Universitas Nasional, 2020)
This research based on the problem of organizational commitment and job satisfaction of employees in the Bantargebang Sub-district environment of Bekasi City, which allegedly the two variables have a causal relationship. Referring to the opinion of Locke, Luthans and Gilmer (in Robbins, 2007), and Allan & Meyer (in Sudarmanto (2009), with a sample of 41 respondents in the Bantargebang Subdistrict environment, the conclusion is that there is a strong enough and significant influence on organizational commitment to job satisfaction staff in Bantargebang Sub-district environment. If each organizational commitment is increased by 1%, there will be an increase in employee job satisfaction by 0.541%.